Media and the Transformation of Religion in South Asia - Babb, Lawrence A.; Wadley, Susan Snow (University of Pennsylvania Press, 2016)
This volume explores the effects of the religious transformation taking place in India as sacred symbols assume the shapes of media images. Lifted from their traditional forms and contexts, many religious symbols, beliefs, and practices are increasingly refracted through such media as god posters, comic books, audio recordings, and video programs. The ten original essays here examine the impact on India's traditional social and cultural structures of printed images, audio recordings, film, and video. Contributors: Lawrence A. Babb, Steve Derné, John Stratton Hawley, Stephen R. Inglis, John T. Little, Philip Lutgendorf, Scott L. Marcus, Frances W. Pritchett, Regula Burckhardt Qureshi, H. Daniel Smith, and Susan S. Wadley